Microparticle-associated tissue factor is recycled by endothelial cells resulting in enhanced surface tissue factor activity - Collier, Mary E. W.; Mah, Pui-Mei; Xiao, Yupei; Maraveyas, Anthony; Ettelaie, Camille (Thrombosis and Haemostasis, 2013)
In this study the uptake of tissue factor (TF)-positive microparticles by endothelial cells and the recycling of the TF component were examined. Human dermal blood endothelial cells (HDBEC) were incubated with microparticles derived from cancer cell lines for up to 6 hours. Measurement of HDBEC cell surface TF antigen revealed two distinct peaks at 30 and 180–240 minutes post-incubation with TF-positive, but not TF-deficient microparticles. However, only the second peak was concurrent with high TF activity as determined by a chromogenic thrombin-generation assay. Annexin V-labelling of HDBEC showed phosphatidylserine exposure following 90 minutes incubation with microparticles, which explains the high TF activity associated with the second antigen peak. Analysis of TF mRNA levels revealed no de novo expression of TF mRNA in response to microparticles, and pre-incubation of cells with cycloheximide did not prevent the appearance of TF. However, blocking endocytosis with a dynamin inhibitor prolonged the disappearance and prevented the reappearance of TF antigen on the cell surface. Incubation of HDBEC with microparticles containing TF-GFP revealed the early co-localisation of TF with Rab4 and Rab5, followed by co-localisation with the late endosomal/trans-Golgi network marker Rab9, and the recycling endosome marker Rab11. siRNAmediated suppression of Rab11 reduced the reappearance of TF on the cell surface. These data suggest a mechanism by which TF-containing microparticles are internalised by endothelial cells and the TF moiety recycled to the cell surface. Together with the exposure of phosphatidylserine, this is capable of inducing a substantial increase in the procoagulant potential of the surface of endothelial cells.
Keywords: Tissue factor; microparticles; endothelial cells; procoagulant activity; recycling; endosome